Segmental Thoracic Spinal Anaesthesia for Modified Radical Mastectomy- A Novel use of Spinal Anaesthesia - Mueed, Khandaker Md Abdul; Ali , Mohammad; Islam , Mohammed Aminul; Jahan , Kazi Israt; Hossain, Mohammad Shakhawat (Journal of Comilla Medical College Teachers' Association, 2025)
Background: Modified radical mastectomy operations are routinely performed under general anesthesia. A variety of local and regional techniques have been described for breast surgery with the goal of reducing the complications associated with general anaesthesia. Objective: To assess the feasibility of segmental thoracic spinal anaesthesia as a sole anesthetic technique for modified radical mastectomy operation. Methods: This study was conducted on 32 cooperative female patients of age group 35-70 year. T5-T6 space was used for the block to be performed. Once the free flow of CSF was confirmed, 1.5 ml of isobaric bupivacaine 0.5% in addition to 20 μg fentanyl were injected. Demographic characteristics of the study population, any coexisting disease, anaesthetic outcome, duration of surgery, degree of intraoperative analgesia, incidence of complications related to segmental thoracic spinal anaesthesia were observed and analysed. Result: Segmental spinal anesthesia was successful in all patients. Out of 32 patients, 29 blocks (90%) were performed using a single attempt of needle insertion and three patients (10%) required a second attempt for introduction of spinal needle into the subarachnoid space. No paresthesia during introduction of the spinal needle or injection of the local anesthetic occurred in any patient. Hypotension was observed in 4 patients (12%) and were managed by injection ephedrine. Two of the four patients complained of nausea during the event of hypotension that resolved after the correction of hypotension with no need for an antiemetic. Bradycardia was manifested in 1 (3 %) of the patients and was treated with a single dose of Inj. Atropine 0.6 mg IV. Two patients complained of respiratory discomfort, but they were relieved with reassurance only. 1 (3 %) patient required intraoperative analgesics and no patient required conversion to general anesthesia. No patients developed postdural puncture headache, postoperative nausea or vomiting, postoperative urine retention. The majority of the patients (94%) were very satisfied with the procedure, were comfortable during surgery and had a quick postoperative recovery. Conclusion: Segmental thoracic spinal anaesthesia is a safe anesthetic technique for modified radical mastectomy operation. J Com Med Col Teachers’ Asso Jan 2025; 29(1): 20-25